Inner fission barriers of uranium isotopes in the deformed relativistic Hartree-Bogoliubov theory in continuum - Zhang 张, Wei 炜; Huang 黄, Jin-Ke 靳岢; Sun 孙, Ting-Ting 亭亭; Peng 彭, Jing 婧; Zhang 张, Shuang-Quan 双全 (Chinese physics C, 2024)
The inner fission barriers of the even-even uranium isotopes from the proton to the neutron drip line are examined using the deformed relativistic Hartree-Bogoliubov theory in continuum. A periodic-like evolution for the ground state shapes is shown with respect to the neutron number, i.e. , spherical shapes at shell closures 126, 184, 258, and prolate dominated shapes between them. Analogous to the shape evolution, the inner fission barriers also exhibit a periodic-like behavior: peaks at the shell closures and valleys in the mid-shells. The triaxial effect on the inner fission barrier is evaluated using triaxial relativistic mean field calculations combined with a simple BCS method for pairing. When the triaxial correction is included, the inner barrier heights show good consistency with available empirical data. Additionally, the evolution from the proton to the neutron drip line aligns with results from the multi-dimensionally constrained relativistic mean field theory. A flat valley in the fission barrier height is predicted around the neutron-rich nucleus U which may play a role of fission recycling in astrophysical r -process nucleosynthesis.